Association of donor small ubiquitin‐like modifier 4 rs237025 genetic variant with tacrolimus elimination in the early period after liver transplantation. (4th October 2017) - Zhang, Tao; Liu, Yuan; Zeng, Rong; Ling, Qi; Wen, Peihao; Fan, Junwei; Peng, Zhihai
Abstract: Backgrounds & Aims: Individualized tacrolimus treatment can improve drug safety and efficacy. In this study, we aimed to investigate the association of donor and recipient small ubiquitin‐like modifier 4 (SUMO4) rs237025 polymorphisms with tacrolimus elimination and the potential mechanism. Methods: A total of 297 liver transplant patients were enrolled in the study. CYP3A5 rs776746 and SUMO4 rs237025 were genotyped using TaqMan SNPs assays. The activity of nuclear factor‐kB (NF‐kB) was evaluated by luciferase assay. The expressions of CYP3A5 were detected by qRT‐PCR and western blotting. Results: Tacrolimus C/D ratios was significantly lower for donor SUMO4 rs237025 AA carriers than AG/GG carriers at weeks 1, 2, 3. In multivariate analysis, donor and recipient CYP3A5 rs776747, donor SUMO4 rs237025 and total bilirubin were independent predictors of tacrolimus C/D ratios in the early post‐transplantation period both in Cohort A and Cohort B. When combined donor CYP3A5 rs776746 and donor SUMO4 rs237025 genotypes, tacrolimus C/D ratios was highly significant at all investigated time points within the four groups. CYP3A5 mRNA expression in liver tissues was significantly higher for AA carriers than AG/GG patients under inflammatory stimuli after liver transplantation (LT). Furthermore, we demonstrated that SUMO4 rs237025 G allele could increase NF‐κB transcriptional activity under inflammatory condition. And activation of NF‐kB suppressed the expression of pregnane X receptor (PXR)‐mediated CYP3A5 gene. Conclusions: Donor SUMO4 rs237025 genetic variant was associated with higher Tac C/D ratios in the early period after LT, which might be related to the down‐regulation of CYP3A5 enzyme through the NF‐kB signalling pathway.